The Effectiveness of Weaving Games on Enhancing Fine Motor Skills in Children: A Creative Approach to Early Childhood Development - Sitorus, Junida Fitriani; Khadijah, Khadijah; Diah Syahfitri, Siska; Daulat, Daulat; Muin Ishak, Wail (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to evaluate the effectiveness of the traditional weaving game in enhancing fine motor skills in early childhood at RA An-Nida’. Using classroom action research with a mixed-method approach (qualitative and quantitative), the study involved 10 children aged 5-6 years. Data were collected through observations, interviews, documentation, and fine motor skill tests before and after the intervention. The results show a significant improvement in the children's fine motor skills, with the average score increasing from 25.4 to 31.7 after participating in the weaving activity. In addition, the game also contributed to improvements in concentration, hand-eye coordination, and creativity. These findings highlight the importance of traditional games as an effective tool to support fine motor development in early childhood education.